Association of DRD2 gene polymorphisms with schizophrenia in the young Bangladeshi population: A pilot study. Issue 10 (October 2020) - Hussain, Md. Saddam; Siddiqui, Shafayet Ahmed; Mondal, Susmita; Millat, Md. Shalahuddin; Marzan, Sadiatul; Uddin, Md. Giash; Aziz, Md. Abdul; Alam, Md. Faruq; Islam, Mohammad Safiqul
Abstract: Purpose: DRD2 gene is considered one of the most important candidate genes for the schizophrenia (SCZ) development due to its role in dopamine signaling and no genetic association study has been conducted yet on the Bangladeshi SCZ patients. The objective of the present study was to investigate the association of DRD2 genetic polymorphisms (rs4648317, rs4936270, and rs7131056) with SCZ in the Bangladeshi population. Patients and methods: This case-control study consisted of 101 SCZ patients and 101 controls. Genotyping was performed by the polymerase chain reaction and restriction fragment length polymorphism (PCR–RFLP) method. Results: The average ages were 22.15 and 22.09 years in patients and controls, respectively (p > 0.05). CT genotype of rs4936270 showed a significantly higher risk for the development of SCZ compared to CC genotype (OR = 2.0, p = 0.023), whereas no association was found for TT genotype. For the dominant model and T allele, rs4936270 showed a higher risk for the development of SCZ (OR = 2.01, p = 0.020; OR = 1.76, p = 0.021, respectively), while the recessive model had no association with SCZ. A statistically significant (OR = 2.70, p = 0.036) higher risk was found for the AA genotype, but no association was found for GA genotype of rs4648317 SNP compared to GG genotype. In case of dominant and recessive models, rs4648317 showed no association with SCZ. 'A' allele of rs4648317 SNP was found to be significantly associated with the elevated risk of SCZ (OR = 1.50, p = 0.044). No association with SCZ of rs7131056 SNP was found for AC, CC genotypes, dominant, recessive, and allele models. Furthermore, from the haplotyping analysis, we found that CAA and TAA haplotypes of rs4936270, rs7131056 and rs4648317 SNPs are associated with SCZ (χ2 = 8.26, p = 0.004; χ2 = 5.31, p = 0.021, respectively). After Bonferroni correction, the association of SCZ did not withstand with any genotype, allele and haplotype (p < 0.017) except CAA haplotype. Conclusion: Our results suggest that DRD2 gene polymorphisms may be associated with the susceptibility of SCZ in the young Bangladeshi population. Abstract : Schizophrenia, Neuropsychiatric disorder, Single nucleotide polymorphism, Haplotypes, Dominant model, Recessive model, Neuroscience, Genetics, Molecular biology, Cancer research, Neurology, Psychiatry, Clinical psychology, Pharmacology, Oncology.